Care Pathway of Venous Thromboembolism (VTE) - Liselotte van Dijk; Linda van Eikenhorst; Mattanja Triemstra; Menno V. Huisman; Cordula Wagner (European Journal of Health Communication (EJHC), 2024)
Deep vein thrombosis (DVT) and pulmonary embolism (PE) are prevalent diseases associated with high morbidity and mortality. This study aimed to explore the experiences and needs of patients and physicians within the care pathway of DVT and PE. Ensuring care pathways match patients’ and physicians’ needs, could positively impact therapy adherence and patient satisfaction. Participants were 34 patients and 18 physicians. The qualitative focus groups occurred face-to-face and on an online discussion forum, utilising a predefined topic list. Focus group transcripts were analysed through deductive thematic analysis. Patients and physicians shared similar needs and experiences with information provision and shared decision making. Differences emerged regarding the adequacy of information provided, follow-up and monitoring of residual complaints, and personalised care. Generally, patients expressed higher levels of dissatisfaction compared to physicians. Our findings reveal a disparity between the perceived quality of care by physicians and patients, with patients expressing needs that diverge from physicians' assumptions. Patients need psychological support following DVT and PE, whereas physicians focus on physical recovery. Treatment intensity could be adjusted to align with patients' preferences. These findings highlight the potential for optimising care for patients and ensuring better outcomes in the management of DVT and PE.